2021
DOI: 10.1186/s12960-021-00567-2
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on the current scenario and forecasting the future demand for medical doctors in South Africa up to 2030: towards equal representation of women

Abstract: Background Increasing feminization of medical professions is well-acknowledged. However, this does not always equate to equitable representation of women within medicine, regarding their socio-demographic indicators, regions, sectors and fields of practice. Thus, this paper quantifies the gap in supply of female medical doctors in relation to demand, towards reaching different gender equity scenarios. Methods A retrospective review of the Health Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…This study showed signi cant gender differences in human resources for the eye health category. Of the 217 workforce, only 83 (38%) of the ophthalmic professionals practicing in the two regions were women; this is somewhat similar to the results found in India, where 42% of health workers were females [23], and South Africa, where 41.6% of medical doctors were women [24]. In contrast to our results, previous studies conducted in 57 countries and 104 countries [25,26] indicated a higher proportion of women employed in the health and social sectors, with an estimated 67% of health workers in the 104 countries analyzed being women [26].…”
Section: Output Of Available Hrehsupporting
confidence: 76%
“…This study showed signi cant gender differences in human resources for the eye health category. Of the 217 workforce, only 83 (38%) of the ophthalmic professionals practicing in the two regions were women; this is somewhat similar to the results found in India, where 42% of health workers were females [23], and South Africa, where 41.6% of medical doctors were women [24]. In contrast to our results, previous studies conducted in 57 countries and 104 countries [25,26] indicated a higher proportion of women employed in the health and social sectors, with an estimated 67% of health workers in the 104 countries analyzed being women [26].…”
Section: Output Of Available Hrehsupporting
confidence: 76%
“…High empathy has been linked with a negative impact on health professionals’ mental health and increased risk for compassion fatigue and burnout ( Wagaman et al, 2015 ; Tiwari et al, 2021 ). There is a view that compassion and empathy are motivators for most entrants into the medical field and an adequate reward for the long hours and training ( Gitto and Trimarchi, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study focuses especially on female medical doctors, due to the following reasons: firstly, there is a large gap between male and female medical doctors, showing that there is no equate to equitable representation of women within the medical field in South Africa, due to gender discrimination and inequality in the health workforce ( Tiwari et al, 2021 ; Alam et al, 2022 ), which might impact on burnout levels in female doctors. Secondly, a recent study showed the high levels of burnout, anxiety and depression in female medical doctors in South Africa, but did not explore female doctors’ mental health and well-being as such ( Naidoo et al, 2020 ; Meier and Kim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Males represented 59.4% of medical doctors registered with the Health Professional Council of South Africa (HPCSA), with females representing 40.6%, resulting in a male-to-female ratio of 1:0.7. [ 18 ]…”
Section: Medical Doctors In Indiamentioning
confidence: 99%